2023
DOI: 10.1007/s00330-023-10085-5
|View full text |Cite
|
Sign up to set email alerts
|

Waiting times between examinations with intravascularly administered contrast media: a review of contrast media pharmacokinetics and updated ESUR Contrast Media Safety Committee guidelines

Aart J. van der Molen,
Ilona A. Dekkers,
Remy W. F. Geenen
et al.

Abstract: The pharmacokinetics of contrast media (CM) will determine how long safe waiting intervals between successive CT or MRI examinations should be. The Contrast Media Safety Committee has reviewed the data on pharmacokinetics of contrast media to suggest safe waiting intervals between successive contrast-enhanced imaging studies in relation to the renal function of the patient. Clinical relevance statement Consider a waiting time between elective contrast-enhanced CT and (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Hepatobiliary GBCA has additional intracellular transient uptake and hepatic excretion into the biliary tree. In patients with severely reduced renal function (estimated glomerular filtration rate (eGFR) < 30 ml/min/1.73 m 2 ) this early elimination half-life can increase up to 30h [ 9 ], which can increase the likelihood of transmetallation. A review of pharmacokinetic data showed the presence of a deep compartment of distribution with long-lasting residual excretion.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatobiliary GBCA has additional intracellular transient uptake and hepatic excretion into the biliary tree. In patients with severely reduced renal function (estimated glomerular filtration rate (eGFR) < 30 ml/min/1.73 m 2 ) this early elimination half-life can increase up to 30h [ 9 ], which can increase the likelihood of transmetallation. A review of pharmacokinetic data showed the presence of a deep compartment of distribution with long-lasting residual excretion.…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacokinetics of ICM should determine the waiting intervals between successive CT or MRI examinations [ 59 ]. In patients with normal or moderately impaired renal function (eGFR > 30 ml/min/1.73 m 2 ), 75% of ICM is excreted within 4 hours of administration.…”
Section: Types and Doses Of Icm Intervals Between Consecutive Dosesmentioning
confidence: 99%
“…A potential risk of contrast-enhanced imaging by using ICM is the occurrence of contrast-induced acute kidney injury (CI-AKI), characterized by a swift deterioration in renal function within days after intravascular exposure to ICM [5]. To minimize the potential for CI-AKI in CEM and dBCT, radiologists commonly utilize screening methods in line with those employed for any contrastenhanced CT examination, given the absence of specific guidelines for breast imaging.…”
mentioning
confidence: 99%
“…To minimize the potential for CI-AKI in CEM and dBCT, radiologists commonly utilize screening methods in line with those employed for any contrastenhanced CT examination, given the absence of specific guidelines for breast imaging. Evaluating serum creatinine in all outpatients is recommended practice to determine the estimated glomerular filtration rate (eGFR) in Italian and Dutch guidelines and an alternative imaging technique without ICM is frequently advised when the eGFR value is ≤ 30 mL/min/1.73 m 2 [5,6]. These recommendations are largely expert-based and driven by practical, logistical reasons within hospital environments.…”
mentioning
confidence: 99%
See 1 more Smart Citation